Corticosteroid insensitivity is reversed by formoterol via phosphoinositide-3-kinase inhibition - Rossios, C (Blackwell Publishing Ltd, 2012)
BACKGROUND AND PURPOSE: Patients with chronic obstructive pulmonary disease (COPD) show a poor response to corticosteroids, which has been linked to oxidative stress. Here we show that the long-acting β(2)-agonist formoterol (FM) reversed corticosteroid insensitivity under oxidative stress via inhibition of phosphoinositide-3-kinase (PI3K) signalling. EXPERIMENTAL APPROACH: Responsiveness to corticosteroids dexamethasone (Dex), budesonide (Bud) and fluticasone propionate (FP) was determined, as IC(50) values on TNF-α-induced interleukin 8 release, in U937 monocytic cell line treated with hydrogen peroxide (H(2)O(2)) or peripheral blood mononuclear cells (PBMCs) from patients with COPD or severe asthma. KEY RESULTS: PBMCs from severe asthma and COPD were less sensitive to Dex compared with those from healthy subjects. Both FM (10(−9) M) and salmeterol (SM, 10(−8) M) reversed Dex insensitivity in severe asthma, but only FM restored Dex sensitivity in COPD. Although H(2)O(2) exposure decreased steroid sensitivity in U937 cells, FM restored responsiveness to Bud and FP while the effects of SM were weaker. Additionally, FM, but not SM, partially inhibited H(2)O(2)-induced PI3Kδ-dependent (PKB) phosphorylation. H(2)O(2) decreased SM-induced cAMP production in U937 cells, but did not significantly affect the response to FM. The reduction of SM effects by H(2)O(2) was reversed by pretreatment with LY294002, a PI3K inhibitor, or IC87114, a PI3Kδ inhibitor. CONCLUSION AND IMPLICATIONS: FM reversed oxidative stress-induced corticosteroid insensitivity and decreased β(2) adrenoceptor-dependent cAMP production via inhibition of PI3Kδ signalling. FM will be more effective than SM, when combined with corticosteroids, for the treatment of respiratory diseases under conditions of high oxidative stress, such as in COPD.